Cross-border mergers & acquisitions: the facts as a guide for international economics - Steven Brakman; Harry Garretsen; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2006)
Using a detailed and large data set on cross-border merger and acquisitions we discuss the relationship between theory and observed empirical characteristics: (i) most FDI is in the form of M&As, (ii) firms engaged in M&As seem to be marketseeking', (iii) M&As come in waves (the most recent wave is still unfolding), (iv) economic integration (international deregulation) stimulated M&As, (v) the size of and inequality between M&As grows over time. Our contention in this chapter is that these stylized facts drive and should drive recent theoretical contributions in the field of international economics that try to understand crossborder mergers and acquisitions. Although some models (notably Neary, 2003) explain a number of the characteristics, a full-fledged model of cross-border M&As that, at least in principle, can deal with all the characteristics is still lacking.
Keywords: F23; 330; Übernahme; Fusion; Direktinvestition; Multinationales Unternehmen; Schätzung; Welt